Islamic Education Policy Reform: Political Dynamics and Curriculum Reorientation in the Merdeka Belajar Era - Alif Fatoni; Bahrul Ulum; Jamaluddin Akbar (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to conduct a multidimensional analysis of Islamic education policy reform in Indonesia (2021-2026) through three main pillars: political-regulatory contestation, curriculum reorientation, and digital governance. Utilizing a Systematic Literature Review (SLR) with the PRISMA protocol, the study synthesizes 60 key policy documents and reputable journal articles. Findings reveal that while madrasas have achieved formal legal equality, "fiscal segregation" persists due to the authority dualism between centralized ministries and decentralized local governments. In the curriculum sector, the "Merdeka Belajar" policy serves as an instrument for the "decolonization of reason," enabling transdisciplinary science-religion integration; however, its effectiveness is hampered by technostructural resistance. Furthermore, digital quality assurance has birthed a formalistic "digital bureaucracy" that shifts the teacher's role to a mere data operator. In conclusion, this research constructs a "Hybrid-Contextual" policy model that synergizes Islamic spirituality with technological advancement within a wasathiyah ethical framework. The implications urge policymakers to reposition quality assurance toward an agile, globally competitive ecosystem rather than mere administrative validation. Strategic recommendations focus on synchronizing cross-sectoral regulations for budget fairness and strengthening digital leadership at the educational unit level to ensure sustainable grassroots reform.